Analisa Faktor-Faktor yang Mempengaruhi Kinerja Karyawan pada Customer Experience Department - Andhika, Rycko (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
The purpose of this study is to find out 1) whether there is an effect of leadership style on employee performance 2) whether there is an effect of motivation on employee perfromance 3) whether there is a employee engagement on employee performance The population in this study were customer experience department. The sample used in this study was 108 respondents. The sampling technique used was nonprobability sample. Overall the results of this study are 1) Leadership style has a significant effect on employee performance, 2) Motivation has a significant effect on employee performance, 3) Employee engagement has a significant effect employee performance.